Penerapan Sanksi Pidana Terhadap Perbuatan Pengalihan Barang Jaminan Fidusia (Studi Kasus Pada Polres Serang Kota) - Wiguna, Rahmat; Irawan, Benny; Yulia, Rena (UI Scholars Hub, 2021)
At this time, many financial institutions (leasing) offer easy credit applications for potential customers. This has attracted consumers to apply for motor vehicle loans, both cars and motorbikes, in leasing companies. However, the problem that has occurred recently in financial institutions is the number of cases concerning the transfer of fiduciary collateral. In fact, the said act has been regulated in statutory regulations which have criminal consequences, namely if the debtor transfers goods or pawns the goods which are guaranteed to be Fiduciary without the creditor's permission, the debtor can be subject to a fiduciary crime. This research aims to determine how the application of criminal sanctions to the act of transferring fiduciary goods and how the law enforcement process against the act of transferring fiduciary collateral at the Police Office of Serang District. This research method uses a normative juridical method using secondary data. Secondary data is used to analyze various laws and regulations in the field of law, regulations regarding fiduciary collateral, books relating to fiduciary and articles.